Analysis of the impact of the armed conflict in Ukraine on the population of Romania - Flavius Cristian Mărcău; Cătălin Peptan; Horaţiu Tiberiu Gorun; Vlad Dumitru Băleanu; Victor Gheorman (Frontiers Media S.A., 2022)
PurposeThe study aims to highlight the behavior of people in a state in the vicinity of a military conflict zone. Specifically, it highlights the psychological behavior of Romanian citizens after the invasion of Ukraine by the Russian Federation. It was considered appropriate to carry out this study, given the novelty of such a situation, since, after the end of the Second World War, Europe has no longer faced major problems of insecurity caused by armed conflicts of this magnitude.MethodsThe study was based on the questionnaire applied to a number of 1,193 people with permanent residence in Romania and a minimum age of 18 years. The data were collected in the beginning phase of the invasion of Ukraine by the troops of the Russian Federation, i.e. between March 1-17, 2022. The aim was to obtain information that would allow the observation of re-spondents' opinions on the conflict in Ukraine and its potential escalation, and on the other hand, to allow the assessment of quality of life, using the WHQOL-BREEF measurement instrument.ResultsBased on the results of the study, the highest average satisfaction among the four domains of WHOQOL-BREF is represented by the "Psychological" domain, of the category of people with the lowest fear about a potential future war between Romania and the Russian Federation (83.62 ± 17.48). On the contrary, the lowest average is represented by the "Environment" domain, for the category of persons who do not feel protected by the fact that Romania is a NATO member state (61.77 ± 20.96).ConclusionsThe results of the study show that the indices of the quality of life of the people in Romania, as a state in the proximity of a military conflict with the potential to escalate, are negatively influenced by the fears of people who believe that the war in Ukraine will escalate into a regional or global conflict, or that the Russian Federation is going to use its nuclear arsenal against Ukraine or another NATO member state.